Delayed fixation of a fractured neck of femur due to the use of dabigatran. Issue 2 (9th July 2013) - Turnbull, Chris; Levy, Nicholas; Parsons, Samuel
Summary: An 82‐year‐old lady was receiving dabigatran for the prevention of stroke in atrial fibrillation. Dabigatran is a new oral anticoagulant. Following a fall, she suffered a fractured neck of femur and acute‐on‐chronic renal impairment. The profound anticoagulation and delayed clearance of dabigatran led to a significant delay in operative intervention. The challenges posed by patients on such anticoagulants requiring emergency surgery are explored.